The disappearance of Astrid Bricard - Lester, Natasha, 1973- (Forever, 2024)
"In 1973, fashion icon Astrid Bricard disappeared at the legendary Versailles designer show-down. All that remained was a scrap of fabric...and a family unraveled. Everyone remembers her daringly short, silver lamé dress. An iconic photo capturing an electric moment, where emerging American designer Astrid Bricard is young, uninhibited, and on the cusp of fashion and feminism's changing landscape. She and fellow designer Hawk Jones are all over Vogue and the disco scene. Yet she can't escape the legacy of being the daughter of Mizza Bricard, infamous "muse" for Christian Dior. Astrid would give anything to take her place among the great houses of couture - on her own terms. I won't inspire it when I can create it. But then Astrid disappeared... Now Astrid's daughter, Blythe, holds what remains of her mother and grandmother's legacies. Of all the Bricard women, she can gather the torn, shredded, and painfully beautiful fabrics of three generations of grief, heartbreak, and abandonment to create something that will shake the foundations of fashion. The only piece that's missing is the one question that no one's been able to answer: What really happened to Astrid?"--